2016
DOI: 10.3390/w8080320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rainfall Intensity and Duration on the First Flush from Parking Lots

Abstract: Urban stormwater with large impervious (paved) areas often produces runoff with a variety of contaminants. Although southern California is among the most urbanized coastal areas in the United States, the effect of rainfall variations on washoff efficiency of contaminants from pervious and impervious surfaces is largely unknown. The goal of this study was to investigate the effect of varying rainfall intensities and duration on runoff composition from highly impervious parking lots. In order to control the trem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Rainfall variables such as rainfall amount, duration, intensity, and antecedent dry periods have been used to determine the relationship between rainfall variables to nutrient and pollutant transport [17][18][19]. For example, a study by Schiff et al [20] on stormwater runoff from parking lots in California, US showed that 18 measured compounds were inversely correlated to rainfall duration where longer rain events decreased the concentrations of the constituents in parking lot runoff. Liu et al [21] found that TN concentration in runoff waters from an N-fertilized field was significantly correlated with rainfall amount as more rainfall generated more N runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall variables such as rainfall amount, duration, intensity, and antecedent dry periods have been used to determine the relationship between rainfall variables to nutrient and pollutant transport [17][18][19]. For example, a study by Schiff et al [20] on stormwater runoff from parking lots in California, US showed that 18 measured compounds were inversely correlated to rainfall duration where longer rain events decreased the concentrations of the constituents in parking lot runoff. Liu et al [21] found that TN concentration in runoff waters from an N-fertilized field was significantly correlated with rainfall amount as more rainfall generated more N runoff.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that road runoff had a relatively higher concentration of COD and TSS, and it was relatively alkaline than the nearby rivers (USEP 1996;Gan et al 2008). It is worth mentioning here that, traffic composition, high rainfall, and dense vegetation can be major players in mitigating traffic-induced heavy metal pollution in the study area (Hwang and Weng 2015;Schiff et al 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Previous research has shown that the first flush mainly occurs in paved urban areas [33][34][35][36][37]. However, a large amount of sediments are discharged from the highland fields of the upper part of the Soyang River basin because of soil erosion during extreme rainfall events.…”
Section: Discussionmentioning
confidence: 99%